Proposal of a social entrepreneurship methodology for the Limoncocha community - Muriel Páez, Miguel Humberto (2019)
This work objective consisted of determining the factors that limit social entrepreneurship in the  Limoncocha Community ,  Sucumbíos province whose study sample  were 54 inhabitants, among them entrepreneurs and non-entrepreneurs, with a notable majority of entrepreneurs. Among the tools to be used were: bibliographic search, interviews with experts, interviews and surveys. As a result, it was found out that the self-perception of each individual exerts an influence on their resistance to risk; money is considered to be a limiting factor and both infrastructure and basic services are the critical point of the community in conjunction with the values and problems within the community.